An innovative A-B process for energy efficient wastewater reclamation : study on a stage - Nur 'Alaiyah Gasali (Nanyang Technological University, 2021)
Currently, the municipal wastewater treatment plant (WWTP) with conventional activated sludge as the core is facing increasing concerns related to the high energy consumption and sludge production. The innovative A-B process, in which A stage is primarily for COD capture by direct anaerobic treatment aiming at enhanced energy recovery, while B stage is for energy-efficient nitrogen removal, provided a feasible solution to address these concerns. In this work, co-treatment of food waste liquid (FWL) and municipal wastewater was conducted by batch and continuous tests to investigate its performance as A stage for enhanced energy recovery. It was found that the addition of FWL by 1% and 3% could achieve better performances of anaerobic treatment considering the criteria of COD removal, CH4 production and C/N ratio for the subsequent B stage, and the corresponding values were 79.82%, 0.83, 103.58 mL and 67.54%, 2.38, 194.15 mL with FWL addition of 1 and 3%, respectively. In the continuous test with the optimized FWL addition of 1 and 3%, the peak COD removal and CH4 production were 45.73%, 46.86 mL and 23.86%, 120.64 mL. It should be noted that the performance of anaerobic treatment for the mixture of FWL and municipal wastewater in the continuous test was not satisfied compared with that in the batch test, which might be ascribed to the short reaction time and accumulation of volatile fatty acid, leading to the low pH and inhibition to the anaerobic microorganisms. Further research in these aspects should be conducted in future work. Consequently, the present results could offer in-depth insights into the co-treatment of FWL and municipal wastewater as an enhanced technology for A stage.